iOS 13 programming for beginners : get started with building iOS apps with Swift 5 and Xcode 11 - Sahar, Ahmad; Clayton, Craig (Packt Publishing, 2020)
Functions and Closures -- Technical requirements -- Understanding functions -- Creating a function -- Using custom argument labels -- Using nested functions -- Using functions as return types -- Using functions as parameters -- Using a guard statement to exit a function early -- Understanding closures -- Simplifying closures -- Summary -- Classes, Structures, and Enumerations -- Technical requirements -- Understanding classes -- Creating a class declaration -- Making an instance of the class -- Making a subclass -- Overriding a superclass method -- Understanding structures